Peran Kepala Sekolah dalam Mengembangkan Kapasitas Tenaga Kependidikan Sebagai Upaya Meningkatkan Pelayanan Administrasi di SMPN 3 Palopo - Jannah, Miftahul; Patawari, Firman; Alimuddin (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The role of the principal in developing the capacity of educational staff is a crucial factor in improving the quality of administrative services in educational institutions. This study aims to analyze the role of the principal in developing the capacity of educational staff and identify factors that influence these efforts in improving the quality of school administrative services. This study used a descriptive qualitative approach with principals and educational staff as subjects. Data were collected through interviews, observations, and documentation studies, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and methods. The results show that the principal plays a strategic role as a leader, manager, and motivator through competency development program planning, administrative training, technology utilization workshops, routine coaching, and periodic performance supervision and evaluation. The main findings indicate that the development of educational staff capacity depends not only on technical training, but also on leadership that encourages continuous coaching, performance monitoring, and the use of technology in administrative services. This study confirms that strengthening the capacity of educational staff through systematic and sustainable principal leadership contributes to improving the effectiveness and quality of school administrative services